Editorial to the Age and Ageing Section - Matek, Ljubica; Poljak Rehlicki, Jasna (Anafora, 2023)
This issue of Anafora contains a section with contributions that have emerged from the CAAS Workshop titled “Representations of Age and Ageing in American Culture” held at the University of Zadar in June 2018.